lternatif Penyelesaian Sengketa Antara Konsumen Dan Pelaku Usaha UMKM Melalui Badan Penyelesaian Sengketa Konsumen Kota Mataram - Istihara Zain, Irma; Haerani, Haerani (JUSTISI, 2024)
This study aims to examine and analyze the implementation of dispute resolution between consumers and MSME business actors through the Mataram City BPSK institution. The research method used is empirical with a statutory and sociological approach. The results of this study indicate that the implementation of out-of-court dispute resolution between consumers and MSMEs business actors through BPSK Kota Mataram is in accordance with the Decree of the Minister of Industry and Trade Number 350/MPP/Kep/2001 concerning the Implementation of BPSK Duties and Authorities which is the procedural law of BPSK in resolve disputes. However, the percentage of consumer disputes and MSMEs business actors that are handled and resolved at BPSK is very minimal due to several factors, namely: Lack of existence related to the existence of the Mataram City BPSK institution among consumers and MSMEs business actors, There are internal dispute resolution efforts carried out by business actors MSMEs, the level of consumer satisfaction with product quality and services for MSME business actors is relatively high. Keyword: Alternative Dispute Resolution; Consumer; Businessmen.